Parameter optimization study and performance analysis of 6S-8P permanent magnet flux switching machine with field excitation for high speed hybrid electric vehicles - Sulaiman, Erwan (2011)
Over the past decade, many automotive companies have been commercializing HEVs. Most of them employ interior permanent magnet synchronous machine (IPMSM) using rare-earth magnet as their main traction drives from viewpoints of high torque and power density and high efficiency over most of operating torque-speed ranges. However, since all permanent magnets (PMs) are located on rotor part, a design approach to ensure mechanical strength of the rotor depends on rib thickness and number of bridges between PMs. The increase in the number of bridges improves the mechanical strength, but reduces the maximum torque of the machine due to an increase in leakage flux of PM. To overcome this problem, 6S-8P permanent magnet flux switching machine with additional field excitation coil is presented. The proposed machine has all active parts on the stator body and a rugged rotor structure suitable for high speed operation. Some design parameter refinements are conducted to this machine in order to elevate maximum torque and maximum power densities. As a result, it is shown that the proposed machine after the design refinements becomes a good candidate for target HEV drive applications.